AN ANALYSIS OF DEIXIS USED BY AN ENGLISH TEACHER AT THE EIGHTH GRADE OF MTSN 1 BANDAR LAMPUNG - Febriyanti, Febriyanti (Lentera: Jurnal Ilmiah Kependidikan, 2016)
This study is aimed to find out the type of deixis used by the teacher in teaching and learning process. The method used in this research is qualitative research. After analyzing the data, the writer found that person deixis is the type of deixis that mostly used by the teacher in teaching ang learning process. The use of deixis, whether it is person deixis, spatial deixis and temporal deixis is good in communication. It can help the speaker easier to deliver his/her opinion or thingking to the listener. In this case, it is between the teacher and the students.